(untitled) (Revista Brasileira Multidisciplinar, 2009)
The present text approaches the limitations of special protection of natural resources in the agricultural properties represented by Legal Forest Reserves (LFR), from their origin to the form they are being tutored now. Their relationships and differentiations are established. Forms for the recompositions and use of LFR are approached. Finally, the arguments of the environmentalists and ruralists are pointed out for the improvement of the institute and its applicability, presenting forms of putting in practice the desirable sustainable development